Improving motor fitness in primary school children through a school based intervention - Milica Blagojević; Borislav Obradović; Zoran Radović; Ivan Đukić; Goran Dimitrić; Milorad Jakšić (Exercise and Quality of Life)
The aim of this study is to establish the effects of specially programmed circuit training on physical fitness in primary school children. A total of 58 (28 girls) primary school children aged 11-13 (experimental group 12.2±1.2, control group 12.4±1.1) years voluntarily participated in this study. Physical fitness of children is assessed based on motor skills, through the following tests: abdominal muscle endurance - Sit-ups test, upper body strength and muscular endurance - Bent-arm hang test, upper-body muscular endurance - Pushups test, muscular strength and power of the lower limbs - Standing broad jump test, agility and speed - 4x10m test and flexibility - Sit and reach test. During the regular classes of physical education, the experimental group conducted a circular training lasting 15-20 minutes, at the same time control group practiced exercises that were in accordance with the plan and program of teaching physical education for a particular teaching unit. The treatment lasted for 15 weeks, with two classes of physical education per week. The results for the standing broad jump indicated significant differences between groups following 15 weeks. Furthermore, the group that participated in the circuit training program made significantly greater gains compared to the control group (p<0.05) in bent-arm hang, sit-ups and sit and reach. The results for the 4x10m test indicated no significant differences in time, group and their interaction (p≥0.05). To conclude, circuit training appears to be an effective way of improving physical fitness in primary school children. The results of this study indicate that this method was more effective for performance than traditional school program.